Detection of Mycobacterium avium subsp. paratuberculosis in liver of slaughtered cattle, sheep and goats by PCR and culture - ZAREI, M; TAJBAKHSH, S; GHORBANPOUR, M; YOUSEFVAND, A; RAHIMI, S; SHAHPOURI, M; AMERI, A; MOSAVARI, N (Journal of the Hellenic Veterinary Medical Society, 2021)
The presence of Mycobacterium avium subsp. paratuberculosis (MAP) in tissues other than intestines and associated lymph nodes is a potential public health concern. Therefore, the presence of MAP in the liver of slaughtered cattle, sheep and goats with unknown Johne’s disease status was evaluated. Liver samples were collected randomly from 470 mature animals including 200 cattle, 135 sheep and 135 goats. The existence of MAP DNA from obtained liver samples was determined using PCR, thereafter PCR-confirmed samples were cultured. Based on liver PCR results, IS900 genes were detected in 11/200 (5.5%), 3/135 (2.2%), 2/135 (1.48%) liver samples of cattle, sheep and goats, respectively. In cattle, sheep and goats, 6 (54.5%), 1 (33.3%) and 1 (50%) PCR-positive samples showed positive results in culture, respectively. Our results revealed that MAP can be detected and cultured from the liver of slaughtered cattle, sheep and goats with unknown Johne’s disease status. Hence, given concerns about a potential zoonotic role for MAP, there is a crucial need to detect animals with MAP disseminated infection in the liver before slaughter.